The digital trainer in the school. NetLogo agent-based simulation model - Luciano Di Mele; Giuseppe Longo (Firenze University Press, 2017)
The article concerns the building of a NetLogo agent-based model to simulate several scenarios regarding the digital school. This analysis tool is based on a systemic vision of the school and is intended to help digital trainers and stakeholders to improve the digitalization process.   L'animatore digitale a scuola. Modello di analisi con simulazione ad agenti in NetLogo L'articolo presenta un modello ad agenti in ambiente NetLogo che permette la simulazione di diversi scenari del processo di digitalizzazione scolastica. L'obiettivo è offrire all'animatore digitale e agli stakeholder uno strumento di analisi basato su una visione sistemica della scuola.